Anlotinib Plus Osimertinib in Osimertinib‐Resistant Nonsquamous Nonsmall Cell Lung Cancer With Gradual Progression: A Retrospective Study - Yu Hua; Minghui Liu; Boshi Li; Hongbing Zhang; Zihe Zhang; Yanan Wang; Jinghao Liu; Xin Li; Yongwen Li; Sen Wei; Hongyu Liu; Jun Chen (Thoracic Cancer)
ABSTRACT Background Previous studies have shown that anlotinib plus third‐generation epidermal growth factor receptor tyrosine kinase inhibitors (EGFR‐TKIs) overcome acquired resistance to EGFR‐TKIs in patients with advanced EGFR‐mutant nonsmall cell lung cancer (NSCLC). This study aimed to retrospectively evaluate whether anlotinib plus osimertinib overcame acquired resistance in patients with nsq‐NSCLC who gradually progressed after first‐line EGFR‐TKI treatment. Methods This study included patients with nsq‐NSCLC who developed gradual progression after first‐line osimertinib treatment, underwent an anlotinib plus osimertinib regimen in Tianjin Medical University General Hospital, and had available data from October 8, 2020 to October 14, 2023. Outcomes included the efficacy, assessed by progression‐free survival (PFS), of anlotinib plus osimertinib treatment (PFS1) and prior osimertinib treatment (PFS2), to disease progression, objective response rate (ORR), disease control rate (DCR), and safety as assessed by the incidence of treatment‐related toxicities. Results A total of 28 patients with nsq‐NSCLC were included, with a median follow‐up of 12 months (range, 7.8–16.2). Treatment with anlotinib plus osimertinib led to a median PFS1 of 10.0 months (95% confidence interval [CI], 8.4–11.6). With a median follow‐up from prior osimertinib therapy of 31.5 months (range, 20.8–42.2), the median PFS2 was 22.0 months (95% CI, 17.5–26.5). The ORR to combination therapy was 3.6% (95% CI, 0.2–20.2) and the DCR was 85.7% (95% CI, 67.3–96.0). All patients experienced treatment‐related toxicities, with 10.7% showing grade 3, and none were grade ≥ 4. Conclusions Anlotinib plus osimertinib exhibited encouraginsg anti‐tumor activity and had a manageable safety profile in patients with nsq‐NSCLC showing gradual progression on osimertinib.